Bringing our best selves to work: Proactive vitality management and strengths use predicting daily engagement in interaction - Pap, Zselyke; Vîrgă, Delia; Lupșa, Daria (Frontiers in Psychology, 2022)
The present research focused on bottom-up, proactive employee behaviors and personal resources that can contribute to more engagement and optimal functioning at work. Based on the Job Demands-Resources (JD-R) and Conservation of Resources (COR) theories, we tested direct and interactive relationships between strengths use (SU), daily proactive vitality management (PVM), and daily work engagement (WE). Eighty-seven (N = 87) employees from a multinational company completed self-reported questionnaires at the beginning of the study and throughout five consecutive workdays (N = 358), yielding a multilevel dataset. We have found a significant daily positive relationship between PVM and WE, which showed significant inter-individual variation and was significantly enhanced by SU at the individual level. This study showed that PVM as employee-initiated proactive behavior and SU as a proactive personal resource facilitate engagement independently but yield the strongest results when used together, suggesting an interactive mechanism between bottom-up effects postulated in the JD-R theory.